Comprehensive solution to the problem of electromagnetic compatibility of modern information and communication systems - Горбенко, І.Д.; Замула, О.А.; Лик, Хо Чі (Radiotekhnika, 2020)
The analysis of the problems of electromagnetic compatibility (EMC) of multi-user information and communication systems (ICS), using code division as a way of providing multiple subscribers access to system resources, in which each subscriber occupies the entire frequency band and the entire time interval. It is shown that the problem of electromagnetic compatibility of ICS as the possibility of a conflict-free existence of various wireless ICS in the conditions when each of these systems has the ability to receive its signals and signals of other systems is one of the highest priorities in the design and operation of such systems. It is shown that EMC requirements can be realized through the use of broadband noise-like signals (BNLS) as synchronization signals and signals – physical data carriers under various interfering influences, including narrow-band, wide-band obstruction, intrasystem (imitated, relayed) and other interferences caused by neighboring stations. This possibility is provided due to the use of signals with a large value of the time-frequency product (signal base) without increasing the signal duration and peak radiation power. Based on the use of the criterion of distinguishability of the signals of the minimum root mean square distance between the signals (vectors), the requirements for the synthesis and selection of the BNLS classes are formulated to ensure that the EMC requirements of multi-user wireless communication systems are met. A new class of complex nonlinear discrete cryptographic signals is proposed as data carrier signals and synchronization signals. It is shown that the use of such signals, due to the fact that they have improved ensemble, correlation, and structural properties, will allow for a comprehensive solution to the EMC problem of modern ICS.